Chronic Tinnitus Exhibits Bidirectional Functional Dysconnectivity in Frontostriatal Circuit - Xu, Jin-Jing; Cui, Jinluan; Feng, Yuan; Yong, Wei; Chen, Huiyou; Chen, Yu-Chen; Yin, Xindao; Wu, Yuanqing (Frontiers in Neuroscience, 2019)
Purpose: The phantom sound of tinnitus is considered to be associated with abnormal functional coupling between the nucleus accumbens (NAc) and the prefrontal cortex, which may form a frontostriatal top-down gating system to evaluate and modulate sensory signals. Resting-state functional magnetic resonance imaging (fMRI) was used to recognize the aberrant directional connectivity of the NAc in chronic tinnitus and to ascertain the relationship between this connectivity and tinnitus characteristics. Methods: Participants included chronic tinnitus patients (n=50) and healthy controls (n=55), matched for age, sex, education, and hearing thresholds. The hearing status of both groups was comparable. On the basis of the NAc as a seed region, a Granger causality analysis study was conducted to investigate the directional connectivity and the relationship with tinnitus duration or distress. Results: Compared to healthy controls, tinnitus patients exhibited abnormal directional connectivity between the NAc and the prefrontal cortex, principally the middle frontal gyrus (MFG), orbitofrontal cortex (OFC), and inferior frontal gyrus (IFG). Additionally, positive correlations between Tinnitus Handicap Questionnaire (THQ) scores and increased directional connectivity from the right NAc to the left MFG (r=0.357, p=0.015) and from the right MFG to the left NAc (r=0.626, p<0.001) were observed. Furthermore, the enhanced directional connectivity from the right NAc to the right OFC was positively associated with the duration of tinnitus (r=0.599, p<0.001). Conclusions: Concurring with expectations, tinnitus distress was correlated with enhanced directional connectivity between the NAc and the prefrontal cortex. The current study not only helps illuminate the neural basis of the frontostriatal gating control of tinnitus sensation but also contribute to deciphering the neuropathological features of tinnitus.